Targeting Epigenetics to Cure HIV-1: Lessons From (and for) Cancer Treatment - Svensson, J. Peter (Frontiers in Cellular and Infection Microbiology, 2021)
The Human Immunodeficiency Virus type 1 (HIV-1) integrates in the host genome as a provirus resulting in a long-lived reservoir of infected CD4 cells. As a provirus, HIV-1 has several aspects in common with an oncogene. Both the HIV-1 provirus and oncogenes only cause disease when expressed. A successful cure of both cancer and HIV-1 includes elimination of all cells with potential to regenerate the disease, while leaving a mass of non-disease causing but mutated cells untouched. For over two decades, epigenetic drugs developed against cancer have been used in the HIV-1 field to modulate the state of the proviral chromatin. Cells with an intact HIV-1 provirus exist in three states of infection: productive, activatable latent, and non-activatable latent. Here focus is on the activatable latently infected cells, how these proviruses are maintained in a chromatin structure that allows inducible transcription and how transcription switches between different stages to allow for an abundance of different transcripts from a single promoter. Recently it was shown that a functional cure of HIV can be achieved by encapsulating all intact HIV-1 proviruses in heterochromatin, giving hope that epigenetic interventions may be used to end the HIV-1 epidemic.